Placenta accreta and emergency cesarean delivery correlates to cervical length and transcervical placental thickness measurement - Shady, Nahla W.; Sallam, Hany F.; Abbas, Ahmed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The study aims to evaluate the effect of cervical length and the transcervical placental thickness measurement at 28-30 weeks gestation in predicting the risk of antepartum haemorrhage (APH) and emergency preterm caesarean delivery (CD) in women with placenta previa accreta. Methods: A prospective cohort study conducted at Aswan university hospital from June 2015 to April 2017 included one hundred and five cases diagnosed as placenta previa accreta by transvaginal ultrasound (TVS) between 28-30 weeks gestation were divided into three groups according to their cervical length which measured by TVS: group I (cervical length >30 mm), group II (cervical length 20-30 mm) and group III (cervical length <20 mm). Also, placental thickness measurement was done. Cervical length and placental thickness and correlated with the clinical outcome regarding to gestational age at delivery, APH, emergency CD due to massive haemorrhage, the need for blood transfusion and caesarean hysterectomy. Results: APH and emergency CD due to massive bleeding were significantly higher in cases with short cervical length and thick placenta. APH occurred in 6 cases (15%) in group I, 14 cases (40%) in group II and 24 cases (80%) in group III, (p=0.0001). Emergency CD in group I was performed in 5 cases (12.5 %), 12 cases (34.3 %) in group II and 24 cases (80%) in group III, (p =0.0001). The incidence of APH was higher in thick placenta [6 cases (42.9 %) compared to none with thin placenta in group I (p=0.001), 13 cases (68.4%) compared to one case (6.2%) in group II (p=0.0001) and 21 cases (100%) compared to 3 cases (33.3%) in group III (p=0.0001)]. Conclusions: Short cervical length and increased placental thickness may predict the risk of APH and emergency preterm CD in patients with placenta accreta.